Testing the Influence of Internal Stem Decay and Topography on Biomass and Carbon Stock Estimates in Mongolia’s Boreal Forest - Choimaa Dulamsuren; Ganbaatar Batsaikhan; Germar Csapek; Steffen Rust; Markus Hauck (Ecosystems, 2026)
The improvement of forest biomass estimates is of outstanding interest to get more detailed information on the global carbon cycle. Forest biomass is usually derived from allometric biomass functions, which rely on the outer shape of the trees (i.e., diameter at breast height [dbh] and tree height). We tested the influence of biomass loss due to internal stem decay and of topography on the aboveground biomass in southern boreal forests of Mongolia. We selected this study area, because the Mongolian boreal forest includes evergreen and deciduous forests (called dark and light taiga) with all gymnosperm genera globally dominating the circumboreal forests. Furthermore, our study could be based on a detailed published carbon stock estimate from this region that was based on allometric regression. We found that internal stem decay and tree cavities caused a significant reduction of the aboveground biomass on the stand level by 5.3%, based on a range of estimates from 4.0 to 6.5%. Moreover, stand biomass was negatively affected by increasing slope inclination, primarily mediated by an influence of inclination on tree height, which cannot be directly captured by upscaling approaches of stand biomass to higher scales with remote sensing-based vegetation indices, but calls for the integration of data from digital terrain models. We developed a new approach of stand aboveground biomass assessments on the basis of linear regression with stand density, mean dbh, and slope inclination as input parameters. This approach leads to similar results as summing up biomass estimates of individual trees from allometric biomass functions.

Geographic variation in resistance of Scots pine (Pinus sylvestris L.) to wind loading across different wind environments in Europe - Andris Seipulis; Barry Gardiner; Heli Peltola; Bruce Nicoll; Steffen Rust; Roberts Matisons; Didzis Elferts; Oskars Krišāns; Aris Jansons (Forest Ecology and Management, 2024)